Optimization of compressor work, power and heat on efficiency refrigerant r290 on split ac - Samsudi Raharjo; RM Bagus Irawan; M. Edi Pujianto (University of Muhammadiyah Jakarta, 2022)
The vapor compression cycle refrigeration machine is the type of refrigeration machine that is most widely used today, generally the medium used as a working fluid that transfers heat from the product being cooled to its environment is a synthetic refrigerant. The working fluid is called refrigerant. Refrigerant is the main working fluid used in air conditioning systems to absorb heat and convert it in the refrigeration system. This then encourages countries in the world including Indonesia to then jointly carry out prevention and improvement by making agreements. Then this agreement was known as the Vienna Convention in 1985 followed by the Montreal agreement in 1987. In order to reduce the impact of ODS (Ozone Depleting Substances), in 1992 Indonesia signed the Montreal protocol. At that time, Indonesia also launched the